Innovation and development of big data ability open platform - Dazhong LI; Jian LIU; Jingwen DENG (大数据)
China Unicom has built a cooperation platform called big data ability open platform based on its own advantages in order to establish a win-win cooperative,coexistent,and sustainable eco-system.The open platform provides variety services in the form of multi-tenancy model for branch companies and partners in aspects of ability access,resource isolation,operation,security,and data services.The open platform satisfies the requirements of internal and external storage capacity and computing ability,data services,and platform tools,thus brings enormous benefits to China Unicom Headquarters.